Extended Adhesion-Sparing Liver Eversion during Kasai Portoenterostomy for Infants with Biliary Atresia - Filippo Parolini; Giovanni Boroni; Pietro Betalli; Maurizio Cheli; Domenico Pinelli; Michele Colledan; Daniele Alberti (MDPI AG, 2021)
Background: Despite the fact that Kasai portoenterostomy (KPE) is the primary treatment for biliary atresia (BA), liver transplantation (LT) remains the ultimate surgery for two-thirds of these patients. Their true survival rate with the native liver reflects the original KPE and the burden of post-operative complications. We report an original modification of the adhesion-sparing liver eversion (ASLE) technique during KPE that facilitates the total native hepatectomy at time of transplantation. Methods: All consecutive patients with BA who underwent KPE at our department and subsequent LT at Paediatric Liver Transplant Centre at Papa Giovanni XXIII Hospital between 2010-2018 were retrospectively enrolled. All patients underwent ASLE during KPE. Patients' demographic data, type of KPE, total transplant time (TTT), hepatectomy time (HT), intra-operative packed red blood cells and plasma transfusions, intra- and post-operative complications were noted. Results: 44 patients were enrolled. Median TTT and HT were 337 and 57 min, respectively. The median volume of packed red blood cell transfusion was 95 mL. No patients presented bowel perforation during the procedure or in the short post-operative course. No mortality after LT was recorded. Conclusions: In addition to the well-known advantages of the standard liver eversion technique, ASLE reduces the formation of intra-abdominal adhesions, lowering significantly the risk of bowel perforation and bleeding when liver transplantation is performed for failure of KPE.